Influence of rapid COVID-19 vaccine development on vaccine hesitancy - ROSENTHAL, Sonny (Institutional Knowledge at Singapore Management University, 2021)
Introduction: In the race to deploy vaccines to prevent COVID-19, there is a need to understand factors influencing vaccine hesitancy. Secondary risk theory is a useful framework to explain this, accounting for concerns about vaccine efficacy and safety. Methods: During the first week of July, 2020, participants (N = 216) evaluated one of three different hypothetical vaccine scenarios describing an FDA-approved vaccine becoming available “next week,” “in one year,” or “in two years.” Dependent variables were perceived vaccine efficacy, self-efficacy, perceived vaccine risk, and vaccination willingness. Covariates included vaccine conspiracy beliefs, science pessimism, media dependency, and perceived COVID-19 risk. Data analysis employed multiple analysis of covariance (MANCOVA). Results: Perceived vaccine efficacy was lowest for the next-week vaccine (η2p =.045). Self-efficacy was higher for the two-year vaccine than the next-week vaccine (η2p =.029). Perceived vaccine risk was higher for the next-week vaccine than for the one-year vaccine (η2p =.032). Vaccination willingness did not differ among experimental treatments. In addition, vaccine conspiracy beliefs were negatively related to perceived vaccine efficacy (η2p =.142), self-efficacy (η2p =.031), and vaccination willingness (η2p =.143) and positively related to perceived vaccine risk (η2p =.216). Conclusions: The rapid development of the COVID-19 vaccine may have heightened public concerns over efficacy, availability, and safety. However, the current findings showed a general willingness to take even the most rapidly developed vaccine. Nonetheless, there remains a need to communicate publicly and transparently about vaccine efficacy and safety and work to reduce vaccine conspiracy beliefs.